Recycling Hierarchical Control Strategy of Conventional Grids for Decentralized Power Supply Systems - Ortjohann, Egon; Sinsukthavorn, Worpong; Lingemann, Max; Hamsic, Nedzad; Hoppe, Marius; Wirasanti, Paramet; Schmelter, Andreas; Jaloudi, Samer; Morton, Danny (IntechOpen, 2012)
None